PENGEMBANGAN INTERAKSI SOSIAL TERHADAP PENDIDIKAN ANAK USIA DINI DALAM PERSPEKTIF ISLAM DI ABAD 21 - Mushab AL Umairi; Agustine Lillawati (Jurnal ADAM : Jurnal Pengabdian Masyarakat, 2023)
The background of this seminar is because of the inability of early childhood in good social interaction in accordance with Islamic teachings towards the environment, school, family and also society in the 21st century (Modernization Era). So, the inability of a child in social interactions that are appropriate to the surrounding environment, can cause children to be isolated from their environment, not to form self-confidence, and others. As a result, the child will experience obstacles in further development. To help reduce the inability of a child in good social interaction. therefore, it takes the efforts of help from adults. In providing this assistance, parents or teachers should understand the process of developing social interaction for early childhood. The benefits of this seminar are considered by adults, both parents and teachers pay attention to good social interaction in accordance with Islamic principles. The targets in this seminar are PAUD institutions in Kel. Central Gununganyar, Kec. Gununganyar, Kota. Surabaya. The activity plan begins with planning including the preparation of materials, determining the place and administration. Then the implementation phase, includes training activities. And the last part is reporting on community service activities. Keywords: Social Interaction, Early Childhood, and Islam